Baking quality of banana-wheat flour blends in four types of cakes - Noval, Ellen Y.
This study was undertaken to determine the baking quality of banana flour substituted at 20% and 40% for wheat flour in two fat-type and in two foam-type cakes. The fat-type cakes were the sponge and the chiffon cakes. An increase in the level of banana flour resulted in a corresponding decrease in the volume of all the cakes. The cake densities, however, showed that the lightness of all the cakes with the two levels of banana flour had little or no difference from that of the control. Texturewise, the pound cake proved to be the best type to use for incorporating banana flour as shown by the indicernible texture difference from that of the control. All the cakes were judged to be acceptable, the lowest score of seven corresponding to like moderately in the Hedonic scale.